Análisis jurídico respecto de la falta de denuncias en delitos flagrantes causando la libertad inmediata de la persona aprehendida - Silva Muñoz, Johanna Katherine (2022)
This degree thesis has been entitled "Legal analysis regarding the lack of complaints in flagrant crimes causing the immediate release of the apprehended person" and its interest in developing is due to the study of criminal recidivism that is caused by the lack of complaints in flagrant crimes, since by not filing the complaint, the apprehended person is released immediately to continue committing crimes, promoting a problem of insecurity in society. In our country there is currently a high rate of crime, society has witnessed how many of the people who have committed crimes have been released immediately, this is because the affected people by flagrant crimes do not carry out the respective accusation in the Government Attorney General's Office, and since there is no complaint by the person who believes he is affected, the apprehended person goes out again to the streets to commit crimes. The study carried out shows that criminal recidivism due to the lack of complaints generates a serious problem in society, putting at risk the legal assets of all people in general, and at the same time makes increasing crime rates. In this thesis, materials and methods that allowed the development of the research, as well as surveys and interviews with legal professionals were applied, whose results were useful to propose the doctrinal reform.